Optimal Design Method of Post-Assembly Magnetizing Device with Field–Circuit Coupling Analysis - Zi-Ang Zhu; Yun-Chong Wang; Xue-Fei Qin; Lei Yao; Johan Gyselinck; Jian-Xin Shen (Actuators, 2023)
Post-assembly magnetization can significantly simplify the manufacturing of the rotor of permanent magnet (PM) electrical machines. The optimization of the post-assembly magnetizing device using finite element analysis (FEA) is time-consuming; therefore, a globally optimal solution aiming at achieving an adequate magnetizing level and minimal energy consumption is difficult to achieve. In this paper, a field–circuit coupling analysis (FCCA) model is proposed to optimize the auxiliary stator-type magnetizing device for interior permanent magnet synchronous machines (IPMSMs). A reasonable simplification of the highly saturated magnetic circuit is made based on FEA results so that the magnetic equivalent circuit (MEC) model can be established. On the other hand, the eddy currents in the PMs are equivalent to an eddy current short-circuit; thus, by converting the field calculation into a circuit calculation, the time cost can be reduced significantly, which greatly improves the speed of multi-objective optimization of the magnetizing device with multiple degrees of freedom. A V-type IPMSM is taken as a study case, and its post-assembly magnetizing device is optimized with the proposed method. FEA and experimental results show that the PMs are fully magnetized, while the required energy consumption is greatly reduced when compared with an existing magnetizing device.